Planning, designing and implementing green infrastructure: A contribution to Alpine spatial planning - Jakob Hüppauff; Hubert Job; Constantin Meyer; Florian Lintzmeyer; Stefan Obkircher; Catarina Proidl; Marco Pütz; Richard Schoßleitner; Günter Salchner; Kerstin Ströbel; Sabine Weizenegger (Verlag der ARL - Akademie für Raumentwicklung in der Leibniz-Gemeinschaft, 2025)
The Alpine region faces particular challenges in implementing the international targets of the Global Biodiversity Framework and the EU Nature Restoration Law. In addition to established components of spatial planning, such as landscape protection or local recreation provision, ecological concerns are increasingly in the spotlight. This position paper from the cross-border working group of the ARL Bavaria Forum considers the multifunctional concept of green infrastructure to be a profitable approach for strengthening the role of spatial planning in the northern Alpine region, specifically with regard to coordinating planning and measures related to open spaces. Such measures and plans have to date been the responsibility of a wide range of specialist departments and are often considered and treated in isolation. At the same time, the intention is also to promote acceptance of government sustainability goals and the effective use of public funds. The position paper outlines a vision of an efficient network of green infrastructure in the Alpine region that, above all, strengthens ecological connectivity and is secured by a spatial planning framework. In order to achieve this, recommendations for action include strengthening the legal framework, ensuring the suitability of planning instruments, promoting and financing measures to implement green infrastructure, strengthening interdepartmental cooperation and mobilising civil social actors.
Keywords: 710; Green infrastructure; Spatial planning; Alpine region; Open space; Intersectoral cooperation; Ecological connectivity